2017
DOI: 10.1111/jpn.12787
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of lysine requirements for growing Japanese quails

Abstract: This study was conducted to estimate the lysine requirements of growing meat-type Japanese quails based on different growth responses using different regression models. Experimental treatments including five doses of dietary lysine (9.40, 10.9, 12.4, 13.9 and 15.4 g/kg of diet) were used in a dose-response platform from 7 to 21 day of age. A total of 375, 7-day old quail chicks were randomly allotted to one of five dietary treatments with five replicate pens and 15 birds per pen. Performance traits including f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…As usual, all protein-containing feed ingredients of basal diet and mixed experimental diets were analyzed for CP method 990.03, 37 and amino acid pro le method 982.30, 37 before beginning the experiment. As described by Hasanvand, et al 7 , feed samples were prepared using a 24-h hydrolysis in 6 N hydrochloric acid at 110°C under an atmosphere of nitrogen. For Met and Cys, performic acid oxidation was done before acid hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As usual, all protein-containing feed ingredients of basal diet and mixed experimental diets were analyzed for CP method 990.03, 37 and amino acid pro le method 982.30, 37 before beginning the experiment. As described by Hasanvand, et al 7 , feed samples were prepared using a 24-h hydrolysis in 6 N hydrochloric acid at 110°C under an atmosphere of nitrogen. For Met and Cys, performic acid oxidation was done before acid hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous data need to be tted by regression models either with linear or quadratic patterns. Among different mathematical models, broken line models are the most prevalent models for determination of nutrient requirements in mammals and poultry [6][7][8][9][10][11][12][13][14] . In general, the broken line models consisted of one or two slope sections and each section may follow the linear and/or quadratic manners in ascending and/or descending orders 6-8, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…As described by Hasanvand et al (2018) , feed samples were prepared using a 24-h hydrolysis in 6 N hydrochloric acid at 110°C under an atmosphere of nitrogen. For Met and Cys, performic acid oxidation was done before acid hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Lys deficiency in early life reduced breast muscle development (Tesseraud, et al 1996) and increased protein degradation in the pectoralis major muscle during the growth period (Tesseraud, et al 2009). Hasanvand, et al (2017) observed that levels below 1.24% Lys, limited the development of quails.…”
Section: Experiments 1 Andmentioning
confidence: 98%
“…Lima, et al (2016) suggested that the ideal Lys level to optimize the growth (1-40 days) of Japanese quail was 1.20%. Hasanvand, et al (2017) observed that levels below 1.24% Lys, limited the development of quails.…”
Section: Introductionmentioning
confidence: 98%